(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The incidence of multi-drug resistance (MDR) in bacteria has become a major problem in this era of modern medicine, making it necessary to look for other options that can be used to treat the infections caused by the MDR bacteria. Scientifically, one of the therapies that is now looking promising, is application of phage therapy. This research work was designed to determine the efficacy of coliphages isolated from sewage, against MDR clinical isolates of E. coli. Ten (10) clinical isolates were subjected to both microbiological conventional and PCR techniques for confirmation, thereafter, the confirmed isolates were tested against some 8 commonly used antibiotics using disk diffusion method to identify the MDR among them. The MDR isolates were subjected to various dilutions (1:10-1:108) of coliphage recovered from sewage, sampled from 5 different locations and isolated by using double agar overlay method. Out of the 10 isolates collected, 8(80%) were confirmed as E. coli, all (8/8: 100%) of which were MDR. However, 6(75%) out of the 8 MDR E. coli, were lysed by the coliphages-observed as cytopathic effect in form of clear zones (plaques) within the bacterial lawn and were recorded from all the dilutions (100%) tested and from all the locations (100%) sampled. Conclusively, infection by MDR E. coli may be life threatening, as it is highly prevalent (100% in our study). However, the coliphages were found to be abundant in sewage and the application of their therapy may provide a good alternative treatment against the MDR.